Exosome-associated AAV2 vector mediates robust gene delivery into the murine retina upon intravitreal injection - Wassmer, Sarah J. (Sci Rep, 2017)
Widespread gene transfer to the retina is challenging as it requires vector systems to overcome physical and biochemical barriers to enter and diffuse throughout retinal tissue. We investigated whether exosome-associated adeno-associated virus, (exo-AAV) enabled broad retinal targeting following intravitreal (IVT) injection, as exosomes have been shown to traverse biological barriers and mediate widespread distribution upon systemic injection. We packaged an AAV genome encoding green fluorescent protein (GFP) into conventional AAV2 and exo-AAV2 vectors. Vectors were IVT injected into the eyes of adult mice. GFP expression was noninvasively monitored by fundus imaging and retinal expression was analyzed 4 weeks post-injection by qRT-PCR and histology. Exo-AAV2 outperformed conventional AAV2 in GFP expression based on fundus image analysis and qRT-PCR. Exo-AAV2 demonstrated deeper penetration in the retina, efficiently reaching the inner nuclear and outer plexiform, and to a lesser extent the outer nuclear layer. Cell targets were ganglion cells, bipolar cells, Müller cells, and photoreceptors. Exo-AAV2 serves as a robust gene delivery tool for murine retina, and the simplicity of production and isolation should make it widely applicable to basic research of the eye.